2011
DOI: 10.1111/j.1464-410x.2010.09482.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity in patients with indwelling ureteric stents: results of a prospective study using the validated Ureteric Stent Symptoms Questionnaire

Abstract: OBJECTIVE:\ud \ud To assess the predictors of morbidity in patients with indwelling ureteric stents using a validated questionnaire.\ud PATIENTS AND METHODS:\ud \ud Eighty-six consecutive patients with indwelling double-J ureteric stent of different length and size enrolled at an Italian tertiary academic centre were prospectively evaluated with the Italian-validated Ureteric Stent Symptoms Questionnaire (USSQ), which explores the stent-related symptoms in six domains. Ureteric stents were placed for benign ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 22 publications
(37 reference statements)
1
99
1
Order By: Relevance
“…Some studies concerning the stent position have argued that crossing the stent distal apart from bladder midline was significantly related to ureteral stent discomforts (7,24). Considering this issue, all of the patients in the present study underwent X-ray imaging after stenting to confirm the proper stent placement.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some studies concerning the stent position have argued that crossing the stent distal apart from bladder midline was significantly related to ureteral stent discomforts (7,24). Considering this issue, all of the patients in the present study underwent X-ray imaging after stenting to confirm the proper stent placement.…”
Section: Discussionmentioning
confidence: 89%
“…Some etiologies have been hypothesized for their complications including mechanical irritation of the bladder trigone, urine renal reflux resulting obstruction, bacterial colonization, stent positioning as well as stent size and design (1,3,(6)(7)(8)(9)(10). Strategies for managing stent complications include accurate stent indications, stenting maneuvers, stent design and use of medications (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that variability in surgical technique could lead to a discrepancy in PRE, based on factors other than the stent string itself. In a recent prospective study using the Ureteric Stent Symptoms Questionnaire (USSQ), the authors found that the most important factors for stent tolerability were gender, with women reporting more of an effect on general health, and whether or not the distal stent coil crossed midline [ 9 ] . The study did not report on whether an extraction string was left in place and did not seek to determine if any intraoperative variables were associated with stent symptoms postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…38 Giannarini et al were the first to investigate this question using the USSQ. 39 They tried to identify predictors of morbidity in a prospective evaluation of 86 patients undergoing temporary ureteral stenting. In a multivariate analysis, the location of the distal stent loop showed the strongest association with most of the USSQ-domains at both 7 and 28 days after insertion.…”
Section: Stent Length and Positionmentioning
confidence: 99%
“…These findings were confirmed by a further small non-randomized trial by Damiano et al 43 Furthermore, other studies investigated stent diameter as a secondary outcome measure, and found no influence on the associated SRS. 39,44 Summarized, although there is a lack of well-designed trials of adequate power, it seems that SRS cannot be influenced by stent diameter.…”
Section: Stent Diametermentioning
confidence: 99%